Variant 1.1.p(x)=p₁(x)+p₂(x)=(x²+2)-(x³-x²-1)=x³+1p₁(x)=x²+2p₂(x)=x³-x²-12.a)2x(x+1)=2x²+2xb)x²y(x-y)=x³y-x²y²3.a)(x-2)²=x²-4x+4b)(3x²+y²)²=9x⁴+6x²y²+y²4.((a⁵+2a⁴-a³)/(-a³))+(a-1)(a+1)=-4(a-1)(a+1)=a²-a+a-1=a²-1-(a⁵+2a⁴-a³)/(a³)=-(a³(a²+2a-1))/(a³)=-(a²+2a-1)-a²-2a+1+a²-1=-2aa=2-2*2=-45.(2x-3)(3x+2)=(x-1)(x+1)+(5x+2)(x-14)(x-1)(x+1)=x²-1(5x+2)(x-14)=5x²-70x+2x-28=5x²-68x-28(2x-3)(3x+2)=6x²+4x-9x-6=6x²-5x-65x²-68x-28+x²-1=6x²-68x-296x²-5x-6=6x²-68x-2963=-23x=-23/63Variant 2.1.p(x)=p₁(x)-p₂(x)=(x²+2x)-(x³+x²-2x)=-x³+4xp₁(x)=x²+2xp₂(x)=x³+x²-2x2.a)3x(x-2)=3x²-6xb)x²y²(x+2y)=x³y²+2x²y³3.a)(2x+4)²=4x²+16x+16b)(x²-2y²)²=x⁴-4x²y²+4y²4.((a²-a⁷+a³)/(-a²))+(a+1)²=-1((a²-a⁷+a³)/(-a²))=-(a²(1-a⁵+a))/(a²)=a⁵-a-1(a+1)²=a²+2a+1a⁵-a-1+a²+2a+1=a⁵+a²+aa=-1(-1)⁵+(-1)²+(-1)=-1+1-1=-15.4(x-4)(x+8)=(3x+2)(x-5)+(x-1)(x+1)(x-1)(x+1)=x²-14(x-4)(x+8)=4(x²+8x-4x-32)=4(x²+4x-32)=4x²+16x-128(3x+2)(x-5)=3x²-15x+2x-10=3x³-13x-103x³-13x-10+x²-1=4x²-13x-114x²+16x-128=4x²-13x-1129x=117x=117/29